Immunohistochemical demonstration of interleukin-17 positivity in skin biopsy specimens of patients with chronic plaque psoriasis and its correlation with severity of psoriasis and associated metabolic syndrome and cardiovascular changes - Madivalara Yallappa Suparna; Praveen Kumar Shanmugam Reddy; Tharayil Kunneth Sumathy; Vijaya V Mysorekar (Wolters Kluwer Medknow Publications, 2022)
Background: Psoriasis is a chronic inflammatory disease which can be associated with metabolic syndrome and cardiovascular abnormalities. Objectives: The aim and objective of the study are to demonstrate interleukin-17 (IL-7) positivity in histopathological sections of psoriatic plaques and to correlate with metabolic syndrome and cardiovascular changes. Materials and Methods: Forty-seven patients with chronic plaque psoriasis with body surface area >10% and psoriasis area and severity index (PASI) score >12, in whom skin biopsy showed munro's microabscesses, were evaluated for IL-17 positivity (intensity and proportion) with associated metabolic syndrome according to the National Cholesterol Education Program adult treatment panel III criteria and cardiovascular comorbidities. A co-relation with PASI score was made. IL-17 intensity and proportion were graded with a score ranging from 0 to 3. IBM SPSS version 16.0 was used for statistical analysis and independent t-test and Chi-square test were used for proportion. Results: The mean age of patients was 43 years. A total of 15 (31.9%) female and 32 (68.1%) male patients were enrolled. The mean PASI score was 21.6. Metabolic syndrome was seen in 31 (65.96%) patients. There was statistically significant association with raised diastolic blood pressure in patients with metabolic syndrome (P = 0.042). The total number of patients with IL-17 positivity with metabolic syndrome was 21 (63.6%). Of these, 9 (42.9%) cases showed IL-17 positivity in the munro's microabscess, 14 (66.7%) cases in the rest of the epidermis, and 18 (85.7%) cases in the dermis. Conclusion: In our study, there was no significant difference in IL-7 positivity between patients with or without metabolic syndrome. Further studies need to be done with large sample size to confirm the significance.